2005
DOI: 10.1002/lsm.20276
|View full text |Cite
|
Sign up to set email alerts
|

Use of lasers and light‐based therapies for treatment of acne vulgaris

Abstract: Over the last two decades, lasers and light-based therapies have been developed to treat a wide variety of cutaneous maladies. Given the prevalence and number of patients who suffer from refractory acne, alternatives to existing care are constantly sought after. In this review, we discuss the evidence currently available to justify the use of laser and light-based modalities and conclude that in combination therapy, such approaches provide a safe and effective treatment for acne vulgaris.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 52 publications
0
54
0
3
Order By: Relevance
“…Laser and light-based therapy potentially clear acne with improvements in acne scarring and skin texture. Nonetheless, these methods are costly and pain causing [77].…”
Section: Tetracyclinesmentioning
confidence: 99%
“…Laser and light-based therapy potentially clear acne with improvements in acne scarring and skin texture. Nonetheless, these methods are costly and pain causing [77].…”
Section: Tetracyclinesmentioning
confidence: 99%
“…Over the last several years, several light-based systems have been employed in the management of acne vulgaris: photodynamic therapy with aminolevulenic acid, blue light alone, pulsed dye laser, KTP laser, several infrared lasers, and radiofrequency devices [6]. These methods are believed to target either P. acnes, the sebaceous glands or both.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to visible wavelengths of light, radiofrequency has also been used to treat acne [22]. Recently, the most commonly used laser modalities for treating acne with electromagnetic radiation are the infrared lasers [23][24][25][26][27][28][29]. These devices were originally developed for dermal remodeling and applied to treatment of rhytides and acne scarring.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most widely used wavelengths for this purpose is the relatively recently developed 1,450 nm diode laser incorporating cryogen spray cooling (Smoothbeam, Candela Corporation, Wayland, MA). Initial studies treating acne scarring with the 1,450 nm diode laser revealed the potential to treat acne, and subsequent studies proved it to be effective at reducing acne [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%